Multifunctional glucose biosensors from Fe(3)O(4) nanoparticles modified chitosan/graphene nanocomposites - Zhang, Wenjing (Sci Rep, 2015)
Novel water-dispersible and biocompatible chitosan-functionalized graphene (CG) has been prepared by a one-step ball milling of carboxylic chitosan and graphite. Presence of nitrogen (from chitosan) at the surface of graphene enables the CG to be an outstanding catalyst for the electrochemical biosensors. The resulting CG shows lower I(D)/I(G) ratio in the Raman spectrum than other nitrogen-containing graphene prepared using different techniques. Magnetic Fe(3)O(4) nanoparticles (MNP) are further introduced into the as-synthesized CG for multifunctional applications beyond biosensors such as magnetic resonance imaging (MRI). Carboxyl groups from CG is used to directly immobilize glucose oxidase (GO(x)) via covalent linkage while incorporation of MNP further facilitated enzyme loading and other unique properties. The resulting biosensor exhibits a good glucose detection response with a detection limit of 16 μM, a sensitivity of 5.658 mA/cm(2)/M, and a linear detection range up to 26 mM glucose. Formation of the multifunctional MNP/CG nanocomposites provides additional advantages for applications in more clinical areas such as in vivo biosensors and MRI agents.